Transmission of knowledge from Mā Warā' Al-Nahr to Nusantara: The central Asia Ulama network and its influence on Islamic intellectual traditions in the Malay archipelago - 18th-19th century - Putra, Achmad Fadel Rusmadi; Robbani, Azmy Subhan; Mubarak, Ahmad Yusuf; Baharuddin,; Hamdani, Ahmad; Muslim, Muhamad Bukhari; Hasyanto,; Mubarak, Ahmad Zaky (Research Journal in Advanced Humanities, 2025)
This study examines the transmission of Islamic knowledge from Central Asia (Mā Warā’ al-Nahr) to the Malay Archipelago (Nusantara), focusing on the role of Central Asia’s ulama networks in shaping Islamic intellectual traditions from the 18th to 19th centuries. Challenging dominant narratives that prioritize the Arab-Haramayn axis, the research repositions Central Asia as a critical yet understudied contributor to Southeast Asia’s Islamic thought. Using socio-intellectual historical analysis, the paper reconstructs scholarly linkages through primary sources such as ijazah (teaching certificates), travelogues, and manuscripts by Nusantara scholars like Nawawi al-Bantani, Abdussamad al-Palimbani, and Yusuf al-Makassari. Findings reveal that Central Asia  influence—mediated through Haramayn scholars—permeated Sufism (notably the Naqshbandiyya order), theology (Maturidi rationalism), and jurisprudence, institutionalized via pesantren curricula and kitab kuning (classical texts). The study identifies three transmission mechanisms: pedagogical certification, textual trade networks, and institutional adaptations of Bukharan educational models. Key results demonstrate how Central Asian ideas were localized, such as the synthesis of Samarqandi catechisms into Malay-Javanese contexts. By highlighting Persianate intellectual currents and non-Arab networks, the research complicates homogenized accounts of Islamization, emphasizing Nusantara’s adaptive agency in transregional knowledge exchange.